2018
DOI: 10.1371/journal.pone.0199387
|View full text |Cite
|
Sign up to set email alerts
|

Forest elephant movement and habitat use in a tropical forest-grassland mosaic in Gabon

Abstract: Poaching of forest elephants (Loxodonta cyclotis) for ivory has decimated their populations in Central Africa. Studying elephant movement can provide insight into habitat and resource use to reveal where, when, and why they move and guide conservation efforts. We fitted 17 forest elephants with global positioning system (GPS) collars in 2015 and 2016 in the tropical forest-grassland mosaic of the Wonga Wongué Presidential Reserve (WW), Gabon. Using the location data, we quantified movement distances, home rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
63
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 40 publications
6
63
1
Order By: Relevance
“…Spatial changes in core home range in relation to water sources were not observed in MFPA—perhaps because year‐round water sources in the interior of the park are more evenly distributed in the form of multiple large rivers. Other recent work has found that forest elephants travel significantly greater distances during the wet season (Mills et al, ), an aspect of ranging behaviour which was not investigated in this study.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Spatial changes in core home range in relation to water sources were not observed in MFPA—perhaps because year‐round water sources in the interior of the park are more evenly distributed in the form of multiple large rivers. Other recent work has found that forest elephants travel significantly greater distances during the wet season (Mills et al, ), an aspect of ranging behaviour which was not investigated in this study.…”
Section: Discussionmentioning
confidence: 67%
“…The lack of a difference in bull and cow range sizes is a notable finding, as previous studies (Plumptre et al, ) into the ranging behaviour of Ugandan elephants (mainly in MFPA) have assumed that bulls roam over much larger distances. Previous literature across Africa has found conflicting results, with some studies reporting that bulls have larger home ranges (Mills et al, ; Shannon, Page, Slotow, & Duffy, ), others finding no difference (Wall, Wittemyer, Klinkenberg, Lemay, & Douglas‐Hamilton, ), and others reporting conflicting results across sites (Blake et al, ). This may in part be explained by the dispersal behaviour of bulls in musth, which will show as a very large home range.…”
Section: Discussionmentioning
confidence: 99%
“…, ), greylag geese ( Anser anser ) could inform us on the existence of permanent – and temporary – water bodies (Kleinhenz and Koenig ), and forest elephants ( Loxodonta cyclotis ) could inform us on both grasslands and forests (Mills et al. ). To achieve this, we encourage research on the environmental requirements of different species and on the link between these requirements and concrete land cover types.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that forest elephants prefer to move at night (Kuwong, ; Turkalo, Wrege, & Wittemyer, ), probably conditioned by the schedules of human activities, and that seasonal displacements of forest elephants are a result of the distribution and fruiting patterns of diet tree species (Blake, ; Mills et al, ; Short, ; White, ). In addition, elephants are known to use bais for access to minerals (Metsio Sienne et al, ), while these sites also function as social arenas where elephants exhibit aggregations (Fishlock, ; Turkalo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, elephants are known to use bais for access to minerals (Metsio Sienne et al, ), while these sites also function as social arenas where elephants exhibit aggregations (Fishlock, ; Turkalo et al, ). It is also known that elephants benefit from herbaceous vegetation in recently logged forests (Clark, Poulsen, Malonga, & Elkan, ; Stokes et al, ) and positively select for this vegetation type during specific seasons (Mills et al, ). By contrast, nonsurveyed roads outside protected areas—which are not patrolled to control hunting or poaching—are formidable barriers to elephant displacements (Blake et al, ; Laurance et al, ).…”
Section: Introductionmentioning
confidence: 99%